Relationships in internationalization of brazilian franchise firms - Sirimarco, Paula Holanda Cavalcanti (2020)
Objective: Understand the role of the relationship between franchisors and franchisees and licensees in the internationalization process adopting the Uppsala model as a theoretical perspective.Methodology/ approach: The methodology used was a case study in three internationalized franchising companies. Subsequently, the information was compared with Uppsala's models (1977, 2009), using franchise and licensing literature as support.Originality / Relevance: Several articles (Dant Grünhagen, 2014; Gomes, Carneiro Secches, 2017; Isaac, Melo, Ogasavara and Rodrigues, 2018) pointed out that the relational theme, especially in the international context, is one of the areas that needs further study. This paper intends to help bridge this gap with information under international partnerships in the licensing and franchise system.Main Results: It has been found that such companies use their knowledge and networks to expand their business and often absorb information from local partners to improve market knowledge and adapt their products or services. The international expansion of the franchising companies studied can be explained by both the original Uppsala Model (1977) and the revisited Uppsala Model (2009).Theoretical/ methodologic contributions: This study aims to contribute from a theoretical point of view when applying the Uppsala Model in international expansions through contractual modes, showing the importance of the relationship network. Both the franchise system and licensing are used for low-cost expansion, which is why the insertion into the local network is essential. With the gradual expansion and solid partnerships, it is noted that companies can validate the business structure and adjust, especially on a cultural level, to their business model.